Cryo-EM insights into tail-anchored membrane protein biogenesis in eukaryotes - Sinning, Irmgard; McDowell, Melanie (Current opinion in structural biology, 2022)
Tail-anchored (TA) proteins are a biologically significant class of membrane proteins, which require specialised cellular pathways to insert their single C-terminal transmembrane domain into the correct membrane. Cryo-electron microscopy has recently provided new insights into the organelle-specific machineries for TA protein biogenesis. Structures of targeting and insertase complexes within the canonical guided entry of TA proteins (GET) pathway indicate how substrates are faithfully chaperoned into the endoplasmic reticulum (ER) membrane in metazoans. The core of the GET insertase is conserved within structures of the ER membrane protein complex (EMC), which acts in parallel to insert a different subset of TA proteins. Furthermore, structures of the dislocases Spf1 and Msp1 show how they remove mislocalised TA proteins from the ER and outer mitochondrial membranes respectively.